Self-injected contraceptives: does the investment reflect women's preferences?. Issue 7 (14th July 2022) - Wood, Shannon N.; Magalona, Sophia; Zimmerman, Linnea A.; OlaOlorun, Funmilola; Omoluabi, Elizabeth; Akilimali, Pierre; Guiella, Georges; Gichangi, Peter; Anglewicz, Philip
Abstract : Subcutaneous depot medroxyprogesterone acetate (DMPA-SC) is an innovative contraceptive method aimed at meeting women's unique circumstances and needs, largely due to its ability to be self-injected. Substantial research and advocacy investments have been made to promote roll-out of DMPA-SC across sub-Saharan Africa. To date, research on the demand for DMPA-SC as a self-injectable method has been conducted largely with healthcare providers, via qualitative research, or with highly specific subsamples that are not population based. Using three recent rounds of data from Performance Monitoring for Action, we examined population-representative trends in demand, use, and preference for self-injection among current non-users in Burkina Faso, the Democratic Republic of Congo (Kinshasa and Kongo Central regions), Kenya, and Nigeria (Lagos and Kano States). We found that while over 80.0% of women had heard of injectables across settings, few women had heard of self-injection (ranging from 13.0% in Kenya to 24.8% in Burkina Faso). Despite initial increases in DMPA-SC prevalence, DMPA-SC usage began to stagnate or even decrease in all settings in the recent three years (except in Nigeria-Kano). Few (0.0%–16.7%) current DMPA-SC users were self-injecting, and the majority instead were relying on a healthcare provider for administration of DMPA-SC. Among current contraceptive non-users wishing to use an injectable in the future, only 1.5%–11.4% preferred to self-inject. Our results show that self-injection is uncommon, and demand for self-injection is very limited across six settings, calling for further qualitative and quantitative research on women's views on DMPA-SC and self-injection and, ultimately, their contraceptive preferences and needs.